Persentase Karkas Ayam Kampung Joper (Jowo Super) Yang Diberi Tepung Serai Wangi (Cymbopogon Nardus) Dalam Ransum - Permadi, Aditia; Anggraeni; Kardaya, Dede (Jurnal Peternakan Nusantara, 2025)
Citronella is a plant from the grass family that has active compounds, namely antibiotics and antioxidants, so it has the potential to be used as a feed additive. The purpose of this study was to examine the effect of giving citronella meal (Cymbopogon nardus) in rations on the percentage of Joper chicken carcasses. This study used a complete randomized design (CRD) with 5 treatments and 4 replicates, where each replicate consisted of five Joper chickens. This data was analyzed by Anova and continued with Duncan Multiple Range-Test, if applicable. The treatments consisted of 1) R0= No provision of citronella meal in the ration, 2) R1= Provision of 2% citronella meal in the ration, 3) R2= Provision of 4% citronella meal in the ration, 4) R3= Provision of 6% citronella meal in the ration, and 5) R4= Provision of 8% citronella meal in the ration. The variables observed in this study were slaughter weight, carcass weight, carcass percentage, chest percentage, thigh percentage, wing percentage, and back percentage. The results of this study showed that giving citronella meal in rations up to 6% (as fed basis, w/w) had a significant effect (P<0.05) on slaughter weight, carcass weight, carcass percentage. Feeding 8% citronella meal showed a significant effect (P<0.05) on the back percentage of Joper chicken. The use of citronella in Joper chickens is limited to 8%, because it is high in fiber (34-36%). The addition of citronella meal up to level 6% in the ration increased weight, carcass weight, carcass percentage, and the 8% of citronella meal increased the back percentage of Joper chicken.